MACMA Islamic Ideology in Chinese Muslim Mosques Towards Universalizing Islam in Malaysia - Alice Sabrina Ismail; Nurul Syaheera Aziz (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Malaysia is the world's 43rd most populous country comprising multi-ethnic and multicultural societies. About half the population is ethnically Malay, with minorities of Chinese, Indians, and indigenous peoples. From this number, Chinese Muslims are minorities in Malaysia, and only 2 per cent of ethnic Chinese are Muslims. Nevertheless, there is a growing trend of accommodating Chinese cultural elements in Islamic preaching in Malaysia. Due to this recent emergence of Chinese Muslim cultural identities, Chinese cultural symbols and Islamic messages are combined to produce a new notion in Malaysian society that 'Chineseness' and Islam are compatible. For that reason, the Chinese Muslim association and dakwah movement in Malaysia, like MACMA (Malaysia Chinese Muslim Association), promulgate a cultural dakwah approach aiming to universalize Islam to spread the Islamic messages and invite non-Muslims to get closer to the Islamic faith. One of the approaches is building Chinese-style mosques throughout Malaysia as a symbol of preaching Islam through Chinese cultural signs and practices. However, no comprehensive studies have elucidated how mosques patronized by the MACMA universalize Islam for Muslims and non-Muslims. Therefore, this paper aims to identify and analyze how MACMA Islamic ideology influences the architectural design elements found in the MACMA mosques as a symbol of cultural dakwah to propagate and teach the values of Islam. This study used the hermeneutic method through the interpretivism paradigm. The two indicators of mosques, form-making, and spatial elements, act as a sign of Islamic values to propagate religious tolerance. The findings indicate how Islamic values and ideology involving the practising of Islah, Ikram, and Ihsan are translated into Mosque architectural elements as a symbol of dakwah to display communal-friendly mosque design. Based on these findings, this study will outline the best mosque design guidelines for designers that can function as a religious sign and symbol for transnational dimensions of cultural dakwah towards unity, equality, and spiritual rejuvenation.